IMPROVING EARLY CHILDHOOD EDUCATOR'S PROFESSIONAL COMPETENCES THROUGH IN-HOUSE EARLY CHILDHOOD CREATIVE LEARNING TRAINING - Rohaeni, Ani; Nurhayati, Sri (Jurnal Empowerment, 2025)
This research describes the efforts made to contribute to the improvement of early childhood educators professional competence to be able to carry out their duties well through the application of in-house training. This study used collaborative action research methods, where researchers collaborate with the school, namely RA Al-Ihsan, with the number of participants as many as 8 Early Childhood Educators. The data collection used are observation, interview, and documentation techniques. The data analysis stage in this study goes through the data coding stage and groups the code into themes. The results showed that: (1) In the initial condition of educators experiencing problems related to professional competence, especially in developing materials and creative learning activities for early childhood. (2) The form and process of implementing in-house training include identifying the needs of participants, ideas or ideas related to implementation techniques, training design, implementation and evaluation, using face-to-face and online training techniques. (3) The professional competence of early childhood education (ECE) educators have improved well. Educators have begun to understand what needs to be owned and prepared by educators in developing creative learning materials and activities for early childhood so that the training form in house training can be used as an alternative to improve the professional competence of ECE educators.